Effect of Probiotic Lactobacillus sp. Dad13 on Humoral Immune Response of Balb/C Mice Infected with Salmonella typhimurium - Kusumawati, Ika Dyah; Harmayani, Eni; Asmara, Widya (Universitas Gadjah Mada, 2006)
An indigenous strain of lactic acid bacterium (LAB) identified as Lactobacillus spp. Dad13 (Dad13), isolatedfrom traditional fermented buffalo milk, was found to be potential as probiotic. The aim of this research was to studythe effect of probiotic Dad13 on humoral immune response of Balb/C mice infected with Salmonella typhimurium. Thespecific objective was to find out the effect of different Dad13 consumption time (before and along with infection of S.typhimurium) on the humoral immune response of Balb/C mice. The experiment was conducted by in vivo trial on 20males of Balb/C mice, age of 6-8 weeks, fed with AIN-93 standard diet. The mice were assigned into 4 groups. Eachgroup received the following treatments, ie. Dad13 only, Dad13 before infection, Dad13 along with infection andSalmonella infection only. A volume of 100 μl Dad13 cell suspensions (1010 CFU/ml) were given by oral forced feedingdaily for a week, at week 3 for group before infection and at week 4 for group of Dad13 only and Dad13 along withinfection. Salmonella infection (109 CFU/ml) was given once orally at week 4 to all groups except group treated withDad13 only. The humoral immune response of Balb/C mice was detected 2 weeks after infection by measuring thetiters of IgG and IgA specific from serum and mucosal intestinal liquid samples using Enzyme-linked ImmunosorbentAssay (ELISA) method. The result indicated that humoral immune response of Balb/C mice consuming Dad13 beforeand along with Salmonella infection were significantly different (p<0.05). Dad13 consumption along with Salmonellainfection increased circulated IgG and IgA as well as secretory IgA. It can be concluded that Dad13 probiotic feedingalong with infection increased humoral immune response more significantly compared to that before infection.Key words : Probiotic, Lactobacillus sp. Dad13, Immune response, Salmonella typhimurium